Phraseme und Sprichwörter in offiziellen Dokumenten des slowenischen Bildungssystems - Kacjan, Brigita (Vestnik za tuje jezike, 2012)
The paper deals with an interesting and important, but hitherto neglected phenomenon, the presence of idioms and proverbs in the Slovenian curricula and/or knowledge catalogues. These are official national documents and at the macro level they set out a framework for language teaching and idioms and proverbs are constituent parts of them, as they are natural, multiword, frequent, stable linguistic units with idiomatic characteristics. They represent a significant part of everyday language and it would be expected that they will be accordingly represented in the curriculum/knowledge catalogues for the language subjects in the entire vertical of the Slovenian school system. In the empirical part, where excerpts from a total of 11 curriculum/knowledge catalogs are cited, it is shown that idioms and proverbs occur in only a very modest size, unsystematically and sporadically, that the related terminology is not uniform and that the methodological guidelines are often only indicated. This presentation is rounded up in the conclusion, where possibilities to improve the unsatisfying state concerning idioms and proverbs are presented.
Keywords: frazemi; tuji jeziki; German; nemščina; Slovene; slovenščina; phraseology; frazeologija; pregovori; učni načrti; katalogi znanja; Slovenia; Slovenija